Novel contribution in online sample cleanup for quantitative determination of Levetiracetam in human plasma by LC-Tandem mass spectrometry - Mostafa, Ahmed Abdalazim (European Journal of Chemistry, 2016)
The aim of this work was to develop and validate a simple, sensitive and rapid method for the quantitation of levetiracetam (LEV) in plasma using LC-Tandem mass spectrometry. Plasma samples were prepared by simple protein precipitation using acetonitrile; atenolol was used as internal standard (IS). Chromatographic separation was done on Luna 5 µm C18(2) (Phenomenex) 50 × 2.0 mm using gradient flow using solvent A (0.1% formic acid) and solvent B (0.1% formic acid in acetonitrile: water, 95:5, v:v). The positive-ion mass spectrometric detection method utilized electrospray ionization and the multiple reaction monitoring (MRM) mode. The MRM ion transitions were170.9 → 140.8 and 267.3 → 145.1 for levetiracetam and atenolol, respectively. The retention time of levetiracetam and atenolol is 3.24 and 2.96 min, respectively. The total run time was 5 min. The assay was validated over a concentration range from 1 to 100 µg/mL. The method was robust (minimal matrix effect), sensitive (LOQ, 1 µg/mL) metabolites and reproducible (The precision and accuracy for both intra- and inter-day were acceptable <15%). The method can be done on traditional LC-MS equipment. The method was effectively applied to single case study receiving toxic dose of LEV.